ANALISIS FAKTOR PSIKOLOGIS, HARGA, DAN KUALITAS PELAYANAN DALAM MENGAMBIL KEPUTUSAN PEMBELIAN IKAN GUPPY PADA ERA PANDEMI COVID-19 DI SOLO RAYA - Achmad Dahlan; Andri Nur Tantiono (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to determine whether the independent variables, namely psychological factors, price, and service quality, affect the dependent variable Purchase Decision of Guppies during the COVID-19 pandemic in Solo Raya. This research includes correlational quantitative research, using 97 respondents from consumers who had bought Guppies in Solo Raya. This research uses a multiple linear regression analysis technique. The results of this study concluded that psychological factors, price, and service quality simultaneously affect purchase decisions. Partially, psychological factors and service quality influence purchase decisions, while price does not influence purchasing decisions. Keywords: Purchase Decision; Psychological Factors; Price; Service Quality